Efficacy and Safety of Cheong-A-Won Gagambang (JCE003) on Knee Osteoarthritis: Randomized Controlled Pilot Trial - Haejin Kong; Jaehui Kang; Hyun Lee (MEDrang Inc., 2022)
Background The aim of this study was to evaluate the effectiveness and safety of Cheong-A-Won Gagambang (JCE003) treatment for degenerative knee osteoarthritis. Methods This was a single-center, randomized, double-blind, placebo-controlled pilot clinical trial. There were 36 adults with degenerative knee osteoarthritis who were randomly allocated into JCE003 1,000 mg, JCE003 2,000 mg, or the placebo group (in a 1:1:1 ratio). The participants received 12 weeks of treatment and had scheduled tests every 6 weeks. The primary outcomes were measured using the Korean Western Ontario and McMaster Universities scale, and the secondary outcomes were measured using the visual analog scale, European quality of life-5-dimensions, patient global impression of change, C-reactive protein, and erythrocyte sedimentation rate. Changes between baseline scores and scores following study completion were analyzed. Results There were 29 participants whose data were analyzed in this study. The change of Korean Western Ontario and McMaster Universities, visual analog scale, European quality of life-5-dimensions scores showed significant improvement in the JCE003 1,000 mg group. The change of patient global impression of change was significantly improved in the placebo group. There were 14 adverse events, but there was no clinically significant relationship with the intake of JCE003 compared with the placebo. Conclusion Taking JCE003 may be effective at improving knee pain in patients with degenerative knee osteoarthritis and appears to be safe. Based on this study, the concentration and feasibility of the test group may be used when conducting a large-scale clinical trial of degenerative knee osteoarthritis in the future.